1) y = 2x⁵ - xy' = 2(x⁵)' - x' = 10x⁴ - 12) y = - 3Sinx + 2Cosxy' = - 3(Sinx)' + 2(Cosx)' = - 3Cosx - 2Sonx3) y = 2/3x³ - x² - 7xy' = 2/3(x³)' - (x²)' - 7(x)' = 2/3 * 3x² - 2x - 7 = 2x² - 2x - 74) y = (x + 2)(x² - 7x + 5)y' = (x + 2)' * (x² - 7x + 5) + (x + 2)(x² - 7x + 5)' = 1 * (x² - 7x + 5) + + (x + 2)(2x - 7) = x² - 7x + 5 + 2x² - 7x + 4x - 14 = 3x² - 10x - 95) y = x² Sinxy' = (x² )' * Sinx + x² * (Sinx)' = 2xSinx + x²Cosx6) y = (3x - 5)⁶y' = [(3x - 5)⁶]' = 6(3x - 5)⁵ * (3x - 5)' = 18(3x - 5)⁵7)
![y=Sin \frac{x}{3}\\\\y'=(Sin \frac{x}{3} )'= Cos \frac{x}{3}*( \frac{x}{3})'= \frac{1}{3} Cos \frac{x}{3} y=Sin \frac{x}{3}\\\\y'=(Sin \frac{x}{3} )'= Cos \frac{x}{3}*( \frac{x}{3})'= \frac{1}{3} Cos \frac{x}{3}](https://tex.z-dn.net/?f=y=Sin \frac{x}{3}\\\\y'=(Sin \frac{x}{3} )'= Cos \frac{x}{3}*( \frac{x}{3})'= \frac{1}{3} Cos \frac{x}{3} )
8)